Gasket for electrochemical device and electrochemical device
Gaskets composed of polybutylene terephthalate with specific compression and water vapor permeability characteristics address the challenge of low water vapor permeability in electrochemical devices, improving sealing efficiency.
Patent Information
- Application Number
- JP2024170719
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing gaskets for electrochemical devices, such as lithium-ion batteries, face challenges in achieving excellent low water vapor permeability.
The use of gaskets made from polybutylene terephthalate (PBT) with a compression rate of 5% or more, and having a water vapor permeability coefficient of less than 0.010g/1000hr, addresses the issue of low water vapor permeability.
This solution effectively reduces water vapor permeability, enhancing the sealing performance of electrochemical devices and preventing moisture intrusion.
Smart Images

Figure 2025060571000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a gasket for an electrochemical device and an electrochemical device. [Background technology]
[0002] 2. Description of the Related Art It is known to use resins such as perfluoroalkoxyalkane (PFA) as sealing members (gaskets) for electrochemical devices such as lithium ion secondary batteries (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-174732 A [Patent Document 2] International Publication No. 2020 / 066050 [Patent Document 3] International Publication No. 2014 / 049645 [Patent Document 4] Patent Publication No. 2021-141045 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present disclosure is to provide a gasket for an electrochemical device that has excellent low water vapor permeability, and an electrochemical device using the same. [Means for solving the problem]
[0005] The present disclosure (1) is a gasket for an electrochemical device that contains polybutylene terephthalate and has a compression rate of 5% or more when installed.
[0006] The present disclosure (2) is a gasket according to the present disclosure (1), in which the compression ratio is less than the rupture compression ratio.
[0007] The present disclosure (3) is the gasket according to the present disclosure (1) or (2), which has a water vapor permeability coefficient of less than 0.010 g / 1000 hr.
[0008] The present disclosure (4) is a gasket in any combination with any of the present disclosures (1) to (3) in contact with an electrolyte.
[0009] The present disclosure (5) is an electrochemical device including a gasket in any combination with any of the present disclosures (1) to (4).
[0010] The present disclosure (6) is a gasket for an electrochemical device that contains a polymer and has a compressibility of 20% or more and 75% or less when installed.
[0011] The present disclosure (7) is a gasket according to the present disclosure (6), in which the compression ratio is less than the rupture compression ratio.
[0012] The present disclosure (8) is a gasket according to the present disclosure (6) or (7), having a water vapor permeability coefficient of less than 0.010 g / 1000 hr.
[0013] The present disclosure (9) is a gasket in any combination with any of the present disclosures (6) to (8) containing a polymer having a fluorine substitution rate of 95% or less.
[0014] The present disclosure (10) is a gasket containing at least one polymer selected from the group consisting of polyethylene, polypropylene, polybutylene terephthalate, and polyphenylene sulfide, in any combination with any of the present disclosures (6) to (9).
[0015] The present disclosure (11) is a gasket in any combination with any of the present disclosures (6) to (10) in contact with an electrolyte.
[0016] The present disclosure (12) is an electrochemical device including a gasket in any combination with any of the present disclosures (6) to (11). Effect of the Invention
[0017] According to the present disclosure, it is possible to provide a gasket for electrochemical devices having excellent low water vapor permeability, and an electrochemical device using the same. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a schematic cross-sectional view showing the configuration of a portion including a gasket of an electrochemical device. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a permeation test fixture used in a water vapor permeation test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] It has been discovered that even when a material that has previously been considered to have poor water vapor permeability is used for a gasket, the water vapor permeability can be reduced by setting the compression ratio when attached to an electrochemical device within a specific range.
[0020] The present disclosure will now be described in detail.
[0021] The present disclosure provides a gasket for an electrochemical device (hereinafter also referred to as gasket (1) of the present disclosure) which contains polybutylene terephthalate (PBT) and has a compression rate of 5% or more when installed. The gasket (1) of the present disclosure has the above-mentioned configuration and is therefore excellent in low water vapor permeability.
[0022] In this specification, unless otherwise specified, the gasket (1) of the present disclosure and the gasket (2) of the present disclosure described below will be collectively referred to as the "gasket of the present disclosure."
[0023] The gasket (1) of the present disclosure has a compression rate of 5% or more when fitted, and in terms of further improving low water vapor permeability, it is preferably 10% or more, more preferably 15% or more, even more preferably 20% or more, even more preferably 25% or more, even more preferably 30% or more, particularly preferably 40% or more, and is preferably less than 75%, more preferably 70% or less, even more preferably 65% or less, and even more preferably less than 65%. The compression ratio can be calculated by the following formula. Compression rate (%) = [(thickness of gasket before compression) - (thickness of gasket in compressed state)] / (thickness of gasket before compression) x 100 When determining the compression ratio of an installed gasket, the cross section of the gasket may be observed in an X-ray while it is installed and compressed, and the thickness of the gasket at the point where the distance between the faces of the part compressed by installation is the shortest may be taken as the thickness of the gasket in its compressed state, and the thickness of the gasket at the point where the thickness is the thickest in the uncompressed part may be taken as the thickness of the gasket before it is compressed. Alternatively, the gasket may be removed from the mounting state and heat treated at 150° C. for 24 hours, after which the thickness of the gasket may be taken as the thickness before the gasket is compressed.
[0024] It is preferable that the gasket (1) of the present disclosure has a compression ratio less than the rupture compression ratio, that is, the compression ratio during installation does not lead to rupture due to compression. The above-mentioned rupture compression ratio is determined as the compression ratio at the time of gasket rupture by conducting a compression test in accordance with JIS K7181:2011 using a circular gasket with a rectangular cross section, with an outer diameter of 17.7±0.1 mm, an inner diameter of 14.2±0.1 mm, and a thickness of 1.6±0.05 mm (L0).
[0025] In order to further improve the low water vapor permeability, the gasket (1) of the present disclosure preferably has a water vapor permeability coefficient of 0.015 g / 1000 hr or less, more preferably less than 0.010 g / 1000 hr, even more preferably 0.009 g / 1000 hr or less, even more preferably 0.008 g / 1000 hr or less, even more preferably 0.007 g / 1000 hr or less, even more preferably 0.006 g / 1000 hr or less, particularly preferably 0.005 g / 1000 hr or less, and may be 0.0001 g / 1000 hr or more. The water vapor permeability coefficient is determined by measuring the mass of water that permeates a circular gasket having a rectangular cross section with an outer diameter of Φ17.7 mm, an inner diameter of Φ14.3 mm, and a thickness of 1.6 mmt under the above-mentioned compression ratio when installed, at 80°C for 1000 hours.
[0026] The gasket (1) of the present disclosure may contain components other than PBT, but is preferably made substantially of PBT. This allows the effects of PBT to be exhibited significantly. "Made substantially of PBT" means that the content of PBT in the gasket is 95.0% by mass or more. The PBT content of the gasket is preferably 98.0 mass% or more, more preferably 99.0 mass% or more, even more preferably 99.5 mass% or more, particularly preferably 99.9 mass% or more, and most preferably 99.95 mass% or more. It is also preferred that the gasket (1) of the present disclosure consists solely of PBT.
[0027] The present disclosure also provides a gasket for electrochemical devices (hereinafter also referred to as gasket (2) of the present disclosure) which contains a polymer and has a compressibility of 20% or more and 75% or less when installed.
[0028] The gasket (2) of the present disclosure has an excellent low water vapor permeability due to a compression ratio during installation of 20% or more and 75% or less. In order to further improve the low water vapor permeability, the compression ratio is preferably 25% or more, more preferably 30% or more, and even more preferably 40% or more, and is more preferably less than 75%, even more preferably 70% or less, even more preferably 65% or less, and particularly preferably less than 65%. The compression ratio can be calculated by the following formula. Compression rate (%) = [(thickness of gasket before compression) - (thickness of gasket in compressed state)] / (thickness of gasket before compression) x 100 When determining the compression ratio of an installed gasket, the cross section of the gasket may be observed in an X-ray while it is installed and compressed, and the thickness of the gasket at the point where the distance between the faces of the part compressed by installation is the shortest may be taken as the thickness of the gasket in its compressed state, and the thickness of the gasket at the point where the thickness is the thickest in the uncompressed part may be taken as the thickness of the gasket before it is compressed. Alternatively, the gasket may be removed from the mounting state and heat treated at 150° C. for 24 hours, after which the thickness of the gasket may be taken as the thickness before the gasket is compressed.
[0029] It is preferable that the gasket (2) of the present disclosure has a compression ratio less than the rupture compression ratio, that is, the compression ratio during installation does not lead to rupture due to compression. The above-mentioned rupture compression ratio is determined as the compression ratio at the time of gasket rupture by conducting a compression test in accordance with JIS K7181:2011 using a circular gasket with a rectangular cross section, with an outer diameter of 17.7±0.1 mm, an inner diameter of 14.2±0.1 mm, and a thickness of 1.6±0.05 mm (L0).
[0030] In order to further improve the low water vapor permeability, the gasket (2) of the present disclosure preferably has a water vapor permeability coefficient of less than 0.010 g / 1000 hr, more preferably 0.009 g / 1000 hr or less, even more preferably 0.008 g / 1000 hr or less, even more preferably 0.007 g / 1000 hr or less, even more preferably 0.006 g / 1000 hr or less, particularly preferably 0.005 g / 1000 hr or less, and may be 0.0001 g / 1000 hr or more. The water vapor permeability coefficient is determined by measuring the mass of water that permeates a circular gasket having a rectangular cross section with an outer diameter of Φ17.7 mm, an inner diameter of Φ14.3 mm, and a thickness of 1.6 mmt under the above-mentioned compression ratio when installed, at 80°C for 1000 hours.
[0031] The gasket (2) of the present disclosure contains a polymer, and preferably contains a polymer with a fluorine substitution rate of 95% or less. A polymer with a low fluorine substitution rate has advantages such as low processing costs, ease of processing, and low specific gravity, but may have poor barrier properties against water vapor, etc. The gasket of the present disclosure has excellent low water vapor permeability even when it contains a polymer with a low fluorine substitution rate. The fluorine substitution rate of the polymer can be calculated by the following formula. Fluorine substitution rate (%) = (number of fluorine atoms bonded to carbon atoms constituting the polymer) / ((number of hydrogen atoms bonded to carbon atoms constituting the polymer) + (number of fluorine atoms and chlorine atoms bonded to carbon atoms constituting the polymer)) x 100
[0032] The polymer having a fluorine substitution rate of 95% or less includes a fluoropolymer having a fluorine substitution rate of 95% or less and a non-fluorine polymer (fluorine substitution rate 0%), with the non-fluorine polymer being preferred.
[0033] The fluorine substitution rate of the above fluoropolymer is more preferably 90% or less, even more preferably 70% or less, and even more preferably 50% or less, and is preferably 10% or more, and more preferably 20% or more.
[0034] Examples of the fluoropolymer include ethylene [Et] / tetrafluoroethylene [TFE] copolymer [ETFE], Et / TFE / hexafluoropropylene [HFP] copolymer [EFEP], polychlorotrifluoroethylene [PCTFE], chlorotrifluoroethylene [CTFE] / TFE copolymer, CTFE / TFE / perfluoro(alkyl vinyl ether) [PAVE] copolymer, Et / CTFE copolymer, polyvinyl fluoride [PVF], polyvinylidene fluoride [PVdF], vinylidene fluoride [VdF] / TFE copolymer, VdF / HFP copolymer, and VdF / TFE / HFP. fluororesins such as copolymers, VdF / HFP / (meth)acrylic acid copolymers, VdF / CTFE copolymers, VdF / pentafluoropropylene copolymers, and VdF / PAVE / TFE copolymers; and fluororubbers such as vinylidene fluoride [VdF]-based fluororubbers, tetrafluoroethylene [TFE] / propylene [Pr]-based fluororubbers, TFE / Pr / VdF-based fluororubbers, ethylene [Et] / hexafluoropropylene [HFP]-based fluororubbers, Et / HFP / VdF-based fluororubbers, Et / HFP / TFE-based fluororubbers, fluorosilicone-based fluororubbers, and fluorophosphazene-based fluororubbers.
[0035] Examples of the non-fluorinated polymer include non-fluorinated resins such as polyethylene (PE) such as ultra-high molecular weight polyethylene, polypropylene (PP), polybutylene terephthalate (PBT), and polyphenylene sulfide (PPS); non-fluorinated rubbers such as nitrile rubber, hydrogenated nitrile rubber, styrene-butadiene rubber (SBR), chloroprene rubber (CR), butadiene rubber (BR), natural rubber (NR), isoprene rubber (IR), ethylene-α-olefin rubber, ethylene-α-olefin-non-conjugated diene rubber, chlorinated polyolefin rubber, chlorosulfonated polyolefin rubber, acrylic rubber, ethylene-based acrylic rubber, epichlorohydrin rubber, silicone rubber, butyl rubber (IIR), ethylene-vinyl ester rubber, and ethylene-methacrylate rubber; and crosslinked resins such as phenol resin, epoxy resin, melamine resin, urea resin, unsaturated polyester resin, alkyd resin, silicone resin, polyurethane, and thermosetting resins such as thermosetting polyimide, crosslinked acrylic resin, and crosslinked polyethylene. Of these, non-fluorinated resins are preferred, at least one selected from the group consisting of PE, PP, PBT and PPS is more preferred, and at least one selected from the group consisting of PE, PP and PBT is even more preferred. In particular, at least one selected from the group consisting of PP and PBT is preferred because it has excellent compression resistance. In terms of being more excellent in terms of low water vapor permeability, PE and PP are preferred, and PE is more preferred.
[0036] The PE is preferably an ultra-high molecular weight PE, which has a lower water vapor permeability. The ultra-high molecular weight PE has a weight average molecular weight of 1.0×10 6 More preferably, it is 2.0×10 6 More preferably, it is 7.0×10 or more. 7 It is preferable that the value is less than 7.0×10 6 It is more preferable that: The molecular weight of the ultra-high molecular weight PE is measured by gel permeation chromatography (GPC) in terms of polystyrene.
[0037] Examples of commonly available ultra-high molecular weight PE include Tiber UHMW-PE manufactured by Mitsubishi Chemical Advanced Materials Corporation and Hi-Zex Million manufactured by Mitsui Chemicals, Inc.
[0038] The gasket (2) of the present disclosure may contain components other than the above polymer, but is preferably made substantially of the above polymer. This allows the effects of the above polymer to be significantly exhibited. "Made substantially of the above polymer" means that the content of the above polymer is 95.0% by mass or more relative to the gasket. The content of the above polymer in the gasket is preferably 98.0 mass% or more, more preferably 99.0 mass% or more, even more preferably 99.5 mass% or more, particularly preferably 99.9 mass% or more, and most preferably 99.95 mass% or more. It is also preferred that the gasket (2) of the present disclosure consists solely of the above polymer.
[0039] The gasket of the present disclosure can be manufactured by molding a raw polymer into a desired shape. The form of the raw polymer is not limited and may be a powder, pellet, dispersion, etc., but is preferably a powder or pellet.
[0040] It is preferable to select a raw polymer having a compressibility at break greater than the desired compressibility.
[0041] The method for molding the raw material polymer is not particularly limited, and known molding methods such as cutting, injection molding, extrusion molding, compression molding, etc. Also, a rubber composition containing a rubber and a crosslinking agent (and a crosslinking assistant, if necessary) may be crosslinked and molded by a known method.
[0042] The gasket of the present disclosure is a member used in an electrochemical device to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside.
[0043] The shape of the gasket of the present disclosure is not particularly limited and may be, for example, an annular shape. The gasket of the present disclosure may have a circular, oval, rectangular shape with rounded corners, or the like in a plan view and may have a through hole in the center.
[0044] A usage mode of a gasket according to an embodiment of the present disclosure will be described with reference to the drawings.
[0045] 1, an electrochemical device 10 (for example, a sealed prismatic secondary battery) includes an outer can (not shown) and a lid 1. An electric element (not shown) such as a power generator is housed inside the outer can, and the opening of the outer can is hermetically sealed with the lid 1. The lid 1 is provided with an external terminal 2 (positive terminal or negative terminal), and externally generated power is supplied to an electric element via the external terminal 2 for storage, and also supplied to an external load.
[0046] A gasket 3 for sealing and insulation is provided between the external terminal 2 and the lid 1. The gasket 3 corresponds to the gasket of the present disclosure. Moreover, in order to electrically insulate the external terminal 2 from the lid 1, an insulating plate 4 is provided on the lid 1. The external terminal 2 has a terminal head 21 having a rectangular parallelepiped block shape, and a cylindrical shaft portion 22. The shaft portion 22 protrudes from the lower surface of the terminal head 21 (on the inner side of the electrochemical device).
[0047] As shown in FIG. 1, the gasket 3 has a cylindrical portion 31, a flange portion 32 extending radially from one opening of the cylindrical portion 31, and a side wall portion 33 rising from the periphery of the flange portion 32.
[0048] The cylindrical portion 31 is fitted onto the shaft portion 22 of the external terminal 2, and the inner peripheral surface of the cylindrical portion 31 abuts against the outer peripheral surface of the shaft portion 22. The cylindrical portion 31 is also inserted into the through hole of the lid 1, and the outer peripheral surface of the cylindrical portion 31 abuts against the inner peripheral surface of the through hole of the lid 1.
[0049] The flange portion 32 is sandwiched between the lid 1 and the external terminal 2 , with one contact surface of the flange portion 32 contacting the lower surface of the external terminal 2 and the other contact surface of the flange portion 32 contacting the surface of the lid 1 .
[0050] With the cylindrical portion 31 and the flange portion 32 of the gasket 3 in a compressed state, the gasket 3 comes into contact with the external terminal 2 and the lid 1, thereby ensuring the hermeticity of the electrochemical device.
[0051] The gaskets of the present disclosure are used in electrochemical devices such as batteries and capacitors. The battery may be a secondary battery such as a lithium ion battery. The capacitor is not particularly limited, but is preferably an electrochemical capacitor. Examples of the electrochemical capacitor include an electric double layer capacitor, a hybrid capacitor, and a redox capacitor. Examples of the hybrid capacitor include a sodium ion capacitor, a lithium ion capacitor, and a magnesium ion capacitor. Among these, an electric double layer capacitor is particularly preferred.
[0052] The gasket of the present disclosure can be suitably used as a gasket for batteries, and can be particularly suitably used as a gasket for secondary batteries such as lithium ion batteries.
[0053] The secondary battery may be a secondary battery that uses an electrolyte solution, or may be a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.
[0054] The gasket of the present disclosure is preferably in contact with the electrolyte, i.e., has a contact surface with the electrolyte. Since the gasket of the present disclosure has excellent low water vapor permeability, when used in contact with the electrolyte, it can suppress the intrusion of water into the electrolyte. The electrolyte referred to here includes not only the electrolyte itself provided in the electrochemical device, but also a substance derived from the electrolyte, and may be a liquid, a solid, or a gas. The gas includes, for example, an electrolyte solution that has evaporated, or a gas generated by decomposition of the electrolyte solution during charging and discharging.
[0055] The electrochemical device according to the present disclosure preferably includes a non-aqueous electrolyte. The gasket according to the present disclosure is preferably used in a state of contact with the non-aqueous electrolyte, i.e., has a surface in contact with the non-aqueous electrolyte.
[0056] The non-aqueous electrolyte may be prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts.
[0057] The organic solvent for dissolving the electrolyte salt is not particularly limited, and one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.
[0058] Examples of electrolyte salts include LiClO4, LiAsF6, LiBF4, LiPF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc., and LiPF6, LiBF4, LiN(SO2CF3)2, LiN(SO2C2F5)2, or combinations of these are particularly preferred because of their good cycle characteristics.
[0059] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L.
[0060] The solid electrolyte used in the solid secondary battery may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, the sulfide-based solid electrolyte has the advantage of being flexible.
[0061] The sulfide-based solid electrolyte is not particularly limited, and examples thereof include Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 S 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4(x=0.6~0.8), Li 4+y Ge 1-y Ga y S4(y=0.2~0.3), LiPSCl, LiCl, Li 7-x-2y P.S. 6-x-y Cl x (0.8≦x≦1.7, 0 <y≦-0.25x+0.5)、Li 10 SnP2S 12 Any one selected from the above, or a mixture of two or more of them, can be used.
[0062] The sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.
[0063] The oxide-based solid electrolyte is preferably a compound that contains an oxygen atom (O), has the ionic conductivity of a metal belonging to Group 1 or 2 of the periodic table, and has electronic insulation properties.
[0064] Specific examples of compounds include Li xa La ya TiO3 [xa=0.3~0.7, ya=0.3~0.7] (LLT), Li xb La yb Zr zb M bb mb O nb (M bb is at least one of the elements Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, where xb satisfies 5≦xb≦10, yb satisfies 1≦yb≦4, zb satisfies 1≦zb≦4, mb satisfies 0≦mb≦2, and nb satisfies 5≦nb≦20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, where xc satisfies 0≦xc≦5, yc satisfies 0≦yc≦1, zc satisfies 0≦zc≦1, and nc satisfies 0≦nc≦6. ), Li xd (Al,Ga) yd (Ti,Ge) zd S ad P md O nd (where 1≦xd≦3, 0≦yd≦2, 0≦zd≦2, 0≦ad≦2, 1≦md≦7, 3≦nd≦15), Li (3-2xe) M ee xe D ee O(xe is a number between 0 and 0.1, and M ee represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. xf S yf O zf (1≦xf≦5, 0 <yf≦3、1≦zf≦10)、Li xg S yg O zg (1≦xg≦3, 0 <yg≦2、1≦zg≦10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O 12 , LiPO (4-3 / 2w) Nw (w is w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zinc 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO 2.94 , La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ionic conductor) type crystal structure 12 , Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh S yh P 3-yh O 12 (where 0≦xh≦1, 0≦yh≦1), Li7La3Zr2O with a garnet-type crystal structure 12 (LLZ), etc. Ceramic materials in which elements have been substituted for LLZ are also known. For example, Li 6.24 La3Zr2Al 0.24 O 11.98 , Li 6.25 Al 0.25 La3Zr2O 12 and Li substituted with Ta 6.6 La3Zr 1.6 Ta 0.4 O 12 , Li substituted with Nb 6.75 La3Zr 1.75 Nb 0.25 O 12 Other examples include LLZ-based ceramic materials in which at least one of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) is substituted for LLZ. Phosphorus compounds containing Li, P, and O are also desirable. For example, lithium phosphate (Li3PO4), LiPON, LiPOD, in which part of the oxygen in lithium phosphate is substituted with nitrogen, etc. 1 (D 1is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc. Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 and Li2O-Al2O3-SiO2-P2O5-TiO2.
[0065] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.
[0066] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure. Oxides having a crystalline structure are particularly preferred in terms of good Li-ion conductivity. Examples of oxides having a crystalline structure include perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), garnet type (Li7La3Zr2O 12 (LLZ), etc. Among these, the garnet type is preferred.
[0067] The present disclosure also includes an electrochemical device including the gasket of the present disclosure.
[0068] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES
[0069] The present disclosure will now be described in more detail with reference to examples, but the present disclosure is not limited to these examples.
[0070] Experimental Examples 1-9 <Raw materials> Polypropylene (PP) (product name: Prime Polypro F227, manufactured by Prime Polymer Co., Ltd.) Polybutylene terephthalate (PBT) (Product name: PBT Natural Color Unfilled, manufactured by Kureha Extron Co., Ltd.) Ultra-high molecular weight polyethylene (UHMWPE) (product name: Hi-Zex Million, manufactured by Mitsui Chemicals, Inc.)
[0071] <Break compression ratio (compression ratio at break)> Compression tests were conducted in accordance with JIS K7181:2011 for three types of materials, PP, PBT, and UHMWPE, using annular gaskets with a square cross section, an outer diameter of 17.7±0.1 mm, an inner diameter of 14.2±0.1 mm, and a thickness of 1.6±0.05 mm (L0). The gaskets were compressed to a specified compression ratio, released, and observed under a microscope to determine the rupture compression ratio. The specified compression ratios were 60%, 65%, 70%, 75%, and 80%, in 5% increments, and compression was performed using 10 gaskets of each ratio. The compression ratio at which crazes began to occur on the surface and inside of the gasket based on observation was determined as the rupture compression ratio. The results are shown in Table 1.
[0072] <Test piece> The above polymer was heated to above its melting point to produce a sheet, from which an annular gasket with a square cross section measuring inner diameter Φ14.3 mm × outer diameter Φ17.7 mm × height 1.6 mm was produced.
[0073] <Water vapor permeability test> As shown in Fig. 2, 2 g of water 42 was placed in an aluminum alloy cup 41. A gasket 47 was placed between the cup 41 and a gasket compression jig 43, and a lid 44 was fastened with a bolt 45 to compress the gasket 47. A spacer 46 was placed between the lid 44 and the cup 41, and the compression rate of the gasket 47 was adjusted to 12.5%, 37.5%, or 62.5%. The compression ratio was calculated from the following formula. (Gasket compression rate (%))={1-(distance of the gap (gasket placement portion) between cup 41 and gasket compression jig 43) / (height of gasket before compression)}×100 The mass of the permeation test jig 40 thus obtained was measured. The permeation test jig 40 was placed in an electric furnace at 80°C, and after leaving it for 1000 hours, it was taken out and left at room temperature for 2 hours, after which the mass was measured. The water vapor permeability coefficient was calculated using the following formula. This operation was repeated three times to calculate the average value of the water vapor permeability coefficient. The average value is shown in Table 2. Water vapor permeability coefficient (g / 1000hr) = (mass of permeability test fixture before heating) - (mass of permeability test fixture after heating)
[0074] [Table 1]
[0075] [Table 2] [Explanation of symbols]
[0076] 10: Electrochemical devices 1: Lid 2: External terminal 21:Terminal head 22: Shaft 3: Gasket 31: Cylindrical part 32: Flange part 33: Side wall 4: Insulating plate 40: Transmission test fixture 41: Cup 42:Water 43: Gasket compression tool 44: Lid 45: Bolt 46: Spacer 47: Gasket
Claims
1. A gasket for an electrochemical device, which contains polybutylene terephthalate and has a compression rate of 5% or more when installed.
2. 2. The gasket of claim 1, wherein the compression is less than the rupture compression.
3. 3. The gasket according to claim 1, wherein the water vapor permeability coefficient is less than 0.010 g / 1000 hr.
4. 3. The gasket of claim 1 or 2 in contact with an electrolyte.
5. An electrochemical device comprising the gasket according to claim 1 or 2.
6. A gasket for an electrochemical device comprising a polymer, the gasket having a compressibility of 20% or more and 75% or less when mounted.
7. 7. The gasket of claim 6, wherein the compression is less than the rupture compression.
8. 8. The gasket according to claim 6, having a water vapor permeability coefficient of less than 0.010 g / 1000 hr.
9. 8. The gasket of claim 6 or 7, comprising a polymer having a fluorine substitution rate of 95% or less.
10. 8. The gasket according to claim 6 or 7, comprising at least one polymer selected from the group consisting of polyethylene, polypropylene, polybutylene terephthalate and polyphenylene sulfide.
11. 8. The gasket of claim 6 or 7 in contact with an electrolyte.
12. An electrochemical device comprising the gasket according to claim 6 or 7.
Citation Information
Patent Citations
Sealed battery
JP2010282824A
Cylindrical battery
JP2020074290A
Power storage body
JP2022058294A
Electrode terminal fixing structure, and battery, battery pack and vehicle comprising same
WO2022158864A2
Power storage device
JP2017174732A